2019
DOI: 10.9734/jeai/2019/v34i130163
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Wood Ash Application on Yield Advantage Indices of Maize and Lima Beans in an Intercrop

Abstract: Alternate planting combinations of maize (Zea mays L.) with lima bean (Phaseolus lunatus L.) using wood ash as soil amendments were compared with the sole planting of each crop during the late 2014 and early 2015 planting seasons at the Teaching and Research Farm of the Federal University of Technology, Akure. The experiment in each season adopted three patterns of intercropping using ash as a soil amendment and laid out in a Randomized Complete Block Design (RCBD) with three replications. The experiment compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…These results are also reported by Ajala et al (2019), who state that maize in intercropping systems with lima beans is more productive since it shows a LERt of 1.95 compared to monocultures of these species.…”
Section: Productive Efficiency Of Cropssupporting
confidence: 81%
See 2 more Smart Citations
“…These results are also reported by Ajala et al (2019), who state that maize in intercropping systems with lima beans is more productive since it shows a LERt of 1.95 compared to monocultures of these species.…”
Section: Productive Efficiency Of Cropssupporting
confidence: 81%
“…Therefore, a significant increase in yield was observed compared to the SMxHB and SMxIB crops. In this regard, Ajala et al (2019) observed a reduction in grain yield between 262.20 and 908.9 kg ha -1 in beans in association with maize. When analyzing the total production of both species, the SMxIB association reached 9767.5 kg ha -1 , which was higher than that of SMxHB with a yield of 8897.5 kg ha -1 (Table 2).…”
Section: Maize and Bean Yieldmentioning
confidence: 86%
See 1 more Smart Citation
“…These results represent the role of fertilisers to increasing yield therefore, LER and merits of intercropping when compared to sole cropping in terms of the utilisation of resources for improved plant growth and efficient land utilization. In this context, there were higher LER values, irrespective of the fertiliser level applied as well as the improvement in intercropping relative to sole cropping [60].…”
Section: Discussionmentioning
confidence: 86%
“…The importance of using wood ash with K supplier has been demonstrated in studies. Ajala et al (2019), report that wood ash increased the yield of maize and lima beans. Bonfim-Silva et al (2019) showed that wood ash increased the pH of the soil to adequate values and made K available, resulting in better initial development of cowpea and Bhutia et al (2019) find excellent yields for growing peas.…”
Section: Introductionmentioning
confidence: 99%